Tunable superconductivity by electrochemical intercalation in TaS2. (5th February 2018) - Wang, N Z; Shi, M Z; Shang, C; Meng, F B; Ma, L K; Luo, X G; Chen, X H
Abstract: The controllable manipulation of materials properties has always attracted broad interests since there exists the possibility to identify the relationship between different electronic states, and even discover new states. Here we report the electrochemical intercalation of cetyltrimethylammonium (CTA + ) into 2H–TaS2 . The single layer TaS2 is intercalated with CTA + cations and the direction of CTA + is approximately perpendicular to the lamellar structure of TaS2 . With this facile and efficient method, the superconducting transition temperature ( T c ) of pristine TaS2 increases from 0.8 K to the maximum 3.7 K, showing a dome-like behavior. The Hall coefficient measurement indicates that the intercalated CTA + cations introduce electrons to this system. The present results demonstrate that electrochemical intercalation method is effective in tuning the materials properties and may pave the way for exploring new superconductors.